Global Student Mobility at a Crossroads: Why Data Matters - Martel, Mirka (International Higher Education, 2024)
The profile of globally mobile students has shifted over the last 20 years, and discourse on international higher education today and in the future must take this into account. This article provides insights into trends of student host destinations, the push and pull factors that drive students to study abroad, and the valuable role of comparable host data to identify patterns over time.